THE ESTIMATION OF SELF-INSURANCE LEVEL WITH FOOD IN THE REPUBLIC OF MOLDOVA - Elena ŞCERBACOV (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The purpose of this work consists in estimation of self-insurance level with food of the Republic of Moldova. There would have been Used methodological instruments the analysis and synthesis of conclusive information for the topic approached. The Republic of Moldova is supplied with cereals, except the year 2012, when the level of self-insurance was less than 80 %. The level of self-insurance with sunflower production increased in 2014 compared to 2009 and 2010 years respectively by 116.0 and 80.8 p.p., and compared to 2011 and 2012 it increased by 41.5 and 93.6 p.p. The level of self-insurance with vegetables and melons has been reduced in 2014 compared to 2009 and 2010 by 3.9 and 9.5 p.p. and compared to the years 2011 and 2013 it has reduced respectively by 5.8 and 7.7 p.p. Over-insurance with fruits allows us to increase the volume of export. In the years 2013 and 2014 the Republic of Moldova was not insured with meat production. The Republic of Moldova was insured with eggs, milk and dairy products. In 2014 the degree of covering the necessary of fruits determined on the basis of normatives of average balanced basket is higher than in the years 2010, 2011, 2012 and 2013.